La opción cooperativa para el trabajo de cuidado. Potencialidades y límites para la inserción sociolaboral de mujeres de sectores populares en Argentina - Hopp, Malena Victoria (Universidad Nacional del Litoral, 2021)
The article aims to analyze the cooperative option for care work as a strategy for the socio-labor insertion of women from popular sectors in Argentina. To do this, we use a qualitative methodology based on a case study. The analytical approach proposes to address the tensions and challenges of the sustainability of the cooperative option compared to other strategies: the promotion of individual work mediated by digital platforms and the state promotion of assisted cooperatives. The research shows that the cooperative improves working conditions, provides security and stability; and favors the maintenance and expansion of sources of work. However, there are limitations, on the one hand, due to the restricted nature of the available forms of social protection and security for self-managed work in Argentina; on the other, because of the absence of a market for cooperative cares framed in a comprehensive system. The current context of the COVID-19 pandemic reveals and intensifies both limitations.